Quartzite coal gangue machine-made sand detection method
Through the detection method combined with flotation method and laser scattering method, the problem of excessive stone powder content in quartzite-type coal gangue machined sand is solved, efficient separation and detection is achieved, and the performance of concrete is improved.
Patent Information
- Application Number
- CN202411594446.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-09
- Publication Date
- 2025-02-11
AI Technical Summary
Excessively high gravel powder content in quartzite-type coal gangue machined sand will affect the working performance of concrete, resulting in reduced strength and durability, and the prior art is difficult to effectively remove impurities, resulting in excessive mud content.
The flotation method is used to treat quartzite-type coal gangue mechanism sand, separate it from the stone powder suspension, detect the stone powder content through laser scattering meter, and use collectors, foaming agents and additives to improve the flotation efficiency.
It realizes efficient separation and detection of stone powder in quartzite-type coal gangue machined sand, reduces the powder content of concrete, improves the strength and durability of concrete, and simplifies the detection process.
Smart Images

Figure BDA0005126441510000061 
Figure BDA0005126441510000071
Abstract
Description
Technical Field
[0001] The present application relates to the field of coal gangue machine-made sand, and more specifically, to a method for detecting quartzite coal gangue machine-made sand. Background Art
[0002] In the modern industrial field, especially in the construction of infrastructure such as buildings, roads and bridges, machine-made sand is an important building aggregate, and its quality is directly related to the stability and safety of engineering projects. Quartzite gangue, as a common raw material for machine-made sand, has been widely used in the preparation of machine-made sand due to its high hardness and strong wear resistance. Quartzite gangue refers to the clastic rock sand commonly found in coal strata, which is mainly composed of minerals such as quartz, feldspar, and mica. It is commonly found in coal strata and coexists with coal.
[0003] During the mining and processing of quartzite gangue, it is often contaminated by impurities such as soil and powder. If these impurities are not effectively removed during the preparation process, the mud content of the machine-made sand will be too high. When the machine-made sand with too high mud content is used in building materials such as concrete, its strength and durability will be reduced, thus affecting the quality of the entire project.
[0004] Secondly, in the process of preparing machine-made sand, a large amount of stone powder will be generated in the crushing, screening, grinding and other links. If the stone powder content in quartzite gangue machine-made sand is too high, it will affect the working performance of concrete, such as fluidity, setting time, etc., thereby affecting the construction efficiency and quality. Therefore, it is necessary to test the powder content of quartzite gangue machine-made sand to avoid the adverse effect of excessive powder content on the performance of concrete. Summary of the invention
[0005] In order to solve the above problems, the present application provides a method for detecting quartzite gangue machine-made sand.
[0006] The present application provides a quartzite gangue machine-made sand detection method using the following technical solutions: A method for detecting quartzite gangue machine-made sand comprises the following steps: S1. Taking quartzite gangue machine-made sand as a test sample, separating the quartzite gangue machine-made sand from the stone powder suspension by flotation, and removing the quartzite gangue machine-made sand; S2. Place the separated stone powder suspension in a laser scattering instrument, using a wavelength of 450-700nm, a scattering angle of 15-30°, and a scanning time of 30-40s. Collect the laser scattering data through a computer and compare it with the stone powder content standard curve.
[0007] By adopting the above technical scheme, the quartzite gangue machine-made sand and the stone powder suspension are effectively separated through flotation treatment, and the quartzite gangue machine-made sand is removed, so as to extract the stone powder component to be tested. The laser scattering data collected by the computer is compared and analyzed with the pre-established stone powder content standard curve to determine the stone powder content in the sample. Laser scattering has a high sensitivity to tiny particles. This method can simply and quickly determine whether the stone powder content is qualified.
[0008] Optionally, the method for determining the standard curve of stone powder content is: Prepare a stone powder suspension sample with a content of 1-15%, use a laser scattering instrument to measure the scattered light of the sample with a wavelength of 450-700nm, a scattering angle of 15-30°, and a scanning time of 30-40s. Start scanning from the sample with 1% stone powder content, and measure it every time the stone powder content increases by 1%. Stop after the sample with 15% stone powder content is measured, record the scattered light signal data of each standard sample and draw a standard curve.
[0009] By adopting the above technical solution, by measuring the laser scattering of suspension samples with a stone powder content of 1% to 15%, the scattered light signal data under different stone powder contents can be accurately obtained. After the standard curve is drawn with these data, the stone powder content can be determined by comparing the laser scattering data of the test sample with the standard curve in subsequent tests. This method is simple and fast to operate.
[0010] Optionally, the specific steps of the flotation treatment are: A1. Mix a quartzite gangue machine-made sand sample with water in a weight ratio of 1:(1-3) to form a mortar, add 30-50% of the sample weight of a collector, 20-30% of a foaming agent, and 10-20% of an auxiliary agent to the mortar, and use ultrasonic oscillation to generate bubbles; A2. After the mortar enters the flotation tank, wait for the bubbles to contact and adhere to the stone powder in the mortar, and rise to the water surface with the bubbles to form a foam layer in the flotation tank; A3. Extract the upper foam layer containing stone powder, filter it through a microporous membrane, and then add deionized water to obtain a stone powder suspension.
[0011] By adopting the above technical solution, adding collectors, foaming agents and additives, and combining ultrasonic oscillation to generate bubbles, the stone powder and quartzite gangue machine-made sand can be effectively separated. The bubbles drive the stone powder to rise to the water surface to form a foam layer, thereby achieving an efficient separation effect.
[0012] Optionally, the collector is selected from one of sodium petroleum sulfonate or sodium dodecyl sulfonate.
[0013] By adopting the above technical solution, when sodium petroleum sulfonate is used as a collector, it can increase the hydrophobicity of the surface of mineral particles, reduce the surface tension of the flotation system, and enhance the foaming ability of the flotation system. This helps the mineral particles to combine with bubbles more effectively, thereby improving the flotation efficiency. Sodium dodecyl sulfate can reduce the surface tension between water and solid particles, making the solid particles more easily wetted by water and suspended in water, which helps to achieve effective separation of minerals from stone powder and mud powder during the flotation process.
[0014] Optionally, the frequency of the ultrasonic oscillation is 28-40 kHz, and the treatment is performed for 20-30 minutes.
[0015] By adopting the above technical solution, the frequency of ultrasonic oscillation is in the range of 28-40kHz. When high-frequency ultrasonic waves propagate in the liquid, they can generate strong mechanical vibrations and shock waves. These vibrations and shock waves can effectively disperse the stone powder particles in the mortar, so that the quartzite machine-made sand is effectively separated from the stone powder, thereby improving the flotation efficiency.
[0016] Optionally, the foaming agent is selected from one of pine oil or methyl isobutyl carbinol.
[0017] By adopting the above technical solution, pine oil has excellent foaming performance and stability. It can produce a large number of small and uniform bubbles during the flotation process, which can fully contact the stone powder particles and effectively carry them to the liquid surface to form a foam layer. Methyl isobutyl carbinol also has excellent foaming performance. Its molecular structure enables it to diffuse rapidly in the flotation system and produce abundant bubbles. These bubbles have a large specific surface area and high activity, which can more effectively adsorb stone powder particles and improve flotation efficiency.
[0018] Optionally, the auxiliary agent includes 60-70% copper sulfate and 30-40% calcium carbonate.
[0019] By adopting the above technical solution, the copper ions contained in copper sulfate can chemically adsorb on the surface of stone powder in quartzite gangue machine-made sand, change the electrical properties of the mineral surface, and thus enhance the adhesion between stone powder and bubbles. This chemical adsorption not only improves the flotation efficiency, but also helps to achieve the effective separation of minerals and stone powder. At the same time, the addition of calcium carbonate can also play a buffering role to prevent the flotation effect from being adversely affected by excessive changes in the pH value of the flotation system.
[0020] Optionally, the wavelength used in step S2 is 550-650 nm and the scattering angle is 18-25°.
[0021] By adopting the above technical solution, the laser can effectively penetrate the sample and interact with the stone powder particles to produce a scattering effect. This scattering effect is closely related to the size, shape and distribution of the particles. Therefore, by collecting and measuring the scattered light data and comparing it with the standard curve, the stone powder content can be quickly inferred. Within this scattering angle range, the intensity and distribution characteristics of the scattered light are more obvious, which is conducive to improving the sensitivity and accuracy of the measurement. By precisely controlling the scattering angle, subtle changes in the scattered light can be captured more accurately, thereby achieving accurate measurement of the stone powder content.
[0022] In summary, this application has the following beneficial effects: 1. Since the present application adopts a combination of flotation method and laser scattering method to detect the stone powder content in quartzite gangue machine-made sand, this method has the characteristics of non-contact, high precision, and rapid response, and provides an effective technical means for the detection of powder content in machine-made sand.
[0023] 2. In this application, it is preferred to use a collector to selectively combine with the target mineral, a frother to generate stable bubbles, and an auxiliary agent to adjust the flotation environment to jointly improve the flotation efficiency. This method effectively separates quartzite gangue machine-made sand and stone powder suspension, reducing subsequent processing interference.
[0024] 3. In the present application, it is preferred to perform laser scattering measurement on a suspension sample with a stone powder content of 1% to 15% and draw a standard curve. In subsequent tests, it is only necessary to compare the laser scattering data of the test sample with the standard curve to quickly determine the stone powder content. DETAILED DESCRIPTION
[0025] The present application is further described in detail below with reference to the embodiments. Example
[0026] Example 1 A method for detecting quartzite gangue machine-made sand: The pure stone powder was mixed with 50 ml of deionized water to prepare a standard sample of stone powder suspension with a content of 1-15%, and the scattered light of the sample was measured by using a laser scattering instrument with a wavelength of 620 nm, a scattering angle of 15-30°, and a scanning time of 35 seconds. The scanning started from the standard sample with a stone powder content of 1%, and the measurement was performed every time the stone powder content was increased by 1%. The measurement was stopped after the sample with a stone powder content of 15% was measured, and the scattered light signal data of each standard sample was recorded and a standard curve was drawn; 300 g of sample was randomly taken from a 100 kg quartzite gangue machine-made sand pile, the quartzite gangue machine-made sand sample was mixed with 600 g of water to form a mortar, 90 g of sodium petroleum sulfonate, 60 g of pine oil, and 30 g of additives were added to the mortar, and bubbles were generated by ultrasonic oscillation at a frequency of 38 kHz, and the treatment was performed for 25 min; After the mortar enters the flotation tank, wait for the bubbles to contact and adhere to the stone powder, and rise to the water surface with the bubbles to form a foam layer in the flotation tank. Extract the upper foam layer, pass it through a filter cloth with a pore size of 50μm, and then mix the filtered sediment with 50ml deionized water to form a suspension; The separated stone powder suspension was placed in a laser scattering instrument, using a wavelength of 620 nm, a scattering angle of 15-30°, and a scanning time of 35 s. The laser scattering data was collected by a computer for comparison with the stone powder content standard curve.
[0027] Among them, the auxiliary agents are 20g of copper sulfate and 10g of calcium carbonate.
[0028] Example 2 A method for detecting quartzite gangue machine-made sand: Pure stone powder is respectively mixed with 50 ml of deionized water to prepare a standard sample of stone powder suspension with a content of 1-15%, and a laser scattering instrument is used to measure the scattered light of the sample at a wavelength of 620 nm, a scattering angle of 15-30°, and a scanning time of 35 seconds. The scanning starts from the standard sample with a stone powder content of 1%, and the measurement is performed every time the stone powder content is increased by 1%. The measurement is stopped after the sample with a stone powder content of 15% is measured, and the scattered light signal data of each standard sample is recorded and a standard curve is drawn; 300 g of sample was randomly taken from a 100 kg quartzite gangue machine-made sand pile, the quartzite gangue machine-made sand sample was mixed with 600 g of water to form a mortar, 150 g of sodium petroleum sulfonate, 90 g of pine oil, and 60 g of additives were added to the mortar, and bubbles were generated by ultrasonic oscillation at a frequency of 38 kHz, and the treatment was performed for 25 min; After the mortar enters the flotation tank, wait for the bubbles to contact and adhere to the stone powder, and rise to the water surface with the bubbles to form a foam layer in the flotation tank. Extract the upper foam layer, pass it through a filter cloth with a pore size of 50μm, and then mix the filtered sediment with 50ml deionized water to form a suspension; The separated stone powder and mud powder suspension is placed in a laser scattering instrument, using a wavelength of 620nm, a scattering angle of 15-30°, and a scanning time of 35s. The laser scattering data is collected by a computer for comparison with the stone powder content standard curve.
[0029] Among them, the auxiliary agents are 40g of copper sulfate and 20g of calcium carbonate.
[0030] Example 3 A method for detecting quartzite gangue machine-made sand: Pure stone powder is respectively mixed with 50 ml of deionized water to prepare a standard sample of stone powder suspension with a content of 1-15%, and a laser scattering instrument is used to measure the scattered light of the sample at a wavelength of 620 nm, a scattering angle of 15-30°, and a scanning time of 35 seconds. The scanning starts from the standard sample with a stone powder content of 1%, and the measurement is performed every time the stone powder content is increased by 1%. The measurement is stopped after the sample with a stone powder content of 15% is measured, and the scattered light signal data of each standard sample is recorded and a standard curve is drawn; 300 g of sample was randomly taken from a 100 kg quartzite gangue machine-made sand pile, the quartzite gangue machine-made sand sample was mixed with 600 g of water to form a mortar, 130 g of sodium petroleum sulfonate, 70 g of pine oil, and 50 g of additives were added to the mortar, and bubbles were generated by ultrasonic oscillation at a frequency of 38 kHz, and the treatment was performed for 25 min; After the mortar enters the flotation tank, wait for the bubbles to contact and adhere to the stone powder, and rise to the water surface with the bubbles to form a foam layer in the flotation tank. Extract the upper foam layer, pass it through a filter cloth with a pore size of 50μm, and then mix the filtered sediment with 50ml deionized water to form a suspension; The separated stone powder and mud powder suspension is placed in a laser scattering instrument, using a wavelength of 620nm, a scattering angle of 15-30°, and a scanning time of 35s. The laser scattering data is collected by a computer for comparison with the stone powder content standard curve.
[0031] Among them, the auxiliary agents are 33.3g of copper sulfate and 16.7g of calcium carbonate.
[0032] Example 4 A method for detecting quartzite gangue machine-made sand: Pure stone powder is respectively mixed with 50 ml of deionized water to prepare a standard sample of stone powder suspension with a content of 1-15%, and a laser scattering instrument is used to measure the scattered light of the sample at a wavelength of 620 nm, a scattering angle of 15-30°, and a scanning time of 35 seconds. The scanning starts from the standard sample with a stone powder content of 1%, and the measurement is performed every time the stone powder content is increased by 1%. The measurement is stopped after the sample with a stone powder content of 15% is measured, and the scattered light signal data of each standard sample is recorded and a standard curve is drawn; 5 samples were taken from a 100kg quartzite gangue machine-made sand pile at random positions in the sand pile, 60g of each sample was taken, and 300g of sample was obtained after mixing. The quartzite gangue machine-made sand sample was mixed with 600g of water to form a mortar, 130g of sodium petroleum sulfonate, 70g of pine oil, and 50g of an auxiliary agent were added to the mortar, and bubbles were generated by ultrasonic oscillation. The frequency of the ultrasonic oscillation was 38kHz, and the treatment was performed for 25min. After the mortar enters the flotation tank, wait for the bubbles to contact and adhere to the stone powder, and rise to the water surface with the bubbles to form a foam layer in the flotation tank. Extract the upper foam layer, pass it through a filter cloth with a pore size of 50μm, and then mix the filtered sediment with 50ml deionized water to form a suspension; The separated stone powder and mud powder suspension is placed in a laser scattering instrument, using a wavelength of 620nm, a scattering angle of 15-30°, and a scanning time of 35s. The laser scattering data is collected by a computer for comparison with the stone powder content standard curve.
[0033] Among them, the auxiliary agents are 33.3g of copper sulfate and 16.7g of calcium carbonate.
[0034] Example 5 A method for detecting quartzite gangue machine-made sand: The difference from Example 4 is that the laser wavelength is 550nm.
[0035] Example 6 A method for detecting quartzite gangue machine-made sand: The difference from Example 4 is that the laser wavelength is 650nm.
[0036] Example 7 A method for detecting quartzite gangue machine-made sand: The difference from Example 4 is that the laser scattering angle is 18-25°.
[0037] Example 8 A method for detecting quartzite gangue machine-made sand: The difference from Example 4 is that sodium dodecyl sulfate is used as the collector.
[0038] Example 9 A method for detecting quartzite gangue machine-made sand: The difference from Example 4 is that methyl isobutyl carbinol is used as the foaming agent.
[0039] Comparative Example Comparative Example 1 A method for detecting quartzite gangue machine-made sand: The difference from Example 4 is that no flotation treatment is performed.
[0040] Comparative Example 2 A method for detecting quartzite gangue machine-made sand: The difference from Example 4 is that the separated stone powder suspension is placed in a laser scattering instrument, using a wavelength of 400nm, a scattering angle of 15-30°, and a scanning time of 35s. The laser scattering data is collected by a computer for comparison with the stone powder content standard curve.
[0041] Comparative Example 3 A method for detecting quartzite gangue machine-made sand: The difference from Example 4 is that the separated stone powder and mud powder suspension is placed in a laser scattering instrument, using a wavelength of 620nm, a scattering angle of 10-15°, and a scanning time of 35s. The laser scattering data is collected by a computer for comparison with the stone powder content standard curve.
[0042] Performance testing Detection Methods Quartzite gangue machine-made sands having stone powder contents of 3%, 5% and 10% as determined by the methylene blue method were tested using the methods of Examples 1-9 and Comparative Examples 1-3.
[0043] Table 1 Test results Combining Example 4 and Comparative Example 1 with Table 1, it can be seen that the flotation method can effectively separate the quartzite gangue machine-made sand from the stone powder suspension, which helps to reduce interference factors in subsequent processing steps and make the detection results more accurate.
[0044] It can be seen from Example 4 and Comparative Examples 2-3 and Table 1 that the accuracy of determining the stone powder content is higher when the wavelength is 450-700nm and the scattering angle is 15-30°.
[0045] It can be seen from Examples 1-3 and Table 1 that by changing the dosage of collector, frother and auxiliary agent in the flotation method, the stone powder and machine-made sand can be further separated, thereby improving the subsequent detection accuracy.
[0046] It can be seen from Examples 3 and 4 and Table 1 that by optimizing the random sampling method, the test results can be made more accurate.
[0047] Combining Examples 4-9 and Table 1, it can be seen that using a wavelength of 550-650nm and a scattering angle of 18-25° can effectively penetrate the sample and interact with stone powder and mud powder particles to produce a scattering effect. The effect of using sodium petroleum sulfonate and pine oil is better.
[0048] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed. However, as long as it is within the scope of the claims of the present application, it shall be protected by the patent law.
Claims
1. A method for detecting quartzite gangue machine-made sand, characterized in that: The following steps are involved: S1. Taking quartzite gangue machine-made sand as a test sample, separating the quartzite gangue machine-made sand from the stone powder suspension by flotation, and removing the quartzite gangue machine-made sand; S2. Place the separated stone powder suspension in a laser scattering instrument, using a wavelength of 450-700nm, a scattering angle of 15-30°, and a scanning time of 30-40s. Collect the laser scattering data through a computer and compare it with the stone powder content standard curve.
2. The method for detecting quartzite gangue machine-made sand according to claim 1, characterized in that: The determination method of the stone powder content standard curve is: Prepare a stone powder suspension sample with a content of 1-15%, and use a laser scattering instrument to measure the scattered light of the sample at a wavelength of 450-700nm, a scattering angle of 15-30°, and a scanning time of 30-40s. Start scanning from the sample with 1% stone powder content, and measure it every time the stone powder content increases by 1%. Stop after the sample with 15% stone powder content is measured, record the scattered light signal data of each standard sample and draw a standard curve.
3. The method for detecting quartzite gangue machine-made sand according to claim 1, characterized in that: The specific steps of the flotation process are: A1. Mix the quartzite gangue machine-made sand sample with water in a weight ratio of 1:(1-3) to form a mortar, add 30-50% of the sample weight of a collector, 20-30% of a foaming agent, and 10-20% of an auxiliary agent into the mortar, and use ultrasonic oscillation to generate bubbles; A2. After the mortar enters the flotation tank, wait for the bubbles to contact and adhere to the stone powder in the mortar, and rise to the water surface with the bubbles to form a foam layer in the flotation tank; A3. Extract the upper foam layer containing stone powder, filter it through a microporous membrane, and then add deionized water to obtain a stone powder suspension.
4. The method for detecting quartzite gangue machine-made sand according to claim 3, characterized in that: The collector is selected from one of sodium petroleum sulfonate or sodium dodecyl sulfonate.
5. The method for detecting quartzite gangue machine-made sand according to claim 3, characterized in that: The frequency of the ultrasonic oscillation is 28-40 kHz, and the treatment lasts 20-30 minutes.
6. The method for detecting quartzite gangue machine-made sand according to claim 3, characterized in that: The foaming agent is selected from one of pine oil and methyl isobutyl carbinol.
7. The method for detecting quartzite gangue machine-made sand according to claim 3, characterized in that: The auxiliary agent includes 60-70% copper sulfate and 30-40% calcium carbonate.
8. The method for detecting quartzite gangue machine-made sand according to claim 1, characterized in that: The wavelength used in the S2 step is 550-650 nm and the scattering angle is 18-25°.